2016
DOI: 10.1002/1873-3468.12422
|View full text |Cite
|
Sign up to set email alerts
|

The RNA polymerase I subunit Rpa12p interacts with the stress‐responsive transcription factor Msn4p to regulate lipid metabolism in budding yeast

Abstract: In Saccharomyces cerevisiae, RPA12 encodes the small subunit of RNA polymerase I. Here, we demonstrate that Rpa12p interacts with the transcription factor Msn4p and prevents its binding to the promoter of AYR1 encoding Ayr1p (1-acyldihydroxyacetone phosphate reductase), a key enzyme involved in triacylglycerol biosynthesis and mobilization of nonpolar lipids. Deletion of RPA12 leads to triacylglycerol accumulation due to the binding of Msn4p to the promoter of AYR1 and activation of its transcription. The doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…As the early response is likely to have influential effects on infection outcome, we focused on the four candidate TFs in Group 1 (induction at 0.5 h); the genes CAGL0F00561g, CAGL0G02739g , CAGL0L03157g and CAGL0J04400g are uncharacterized and annotated as the Saccharomyces cerevisiae orthologue of RPA12 , XBP1 , DAL80 , and HAP3 , respectively. Interestingly, three of the yeast orthologues ( RPA12 , XBP1 , DAL80 ) have negative roles in transcription (Mai & Breeden, 1997; Marzluf, 1997; Yadav et al , 2016). Transcription regulatory network analysis by PathoYeastract (Monteiro et al ., 2020) further showed that the orthologues of ∼35% macrophage infection-induced genes (n = 375 out of 1,078, respectively; Figure 2-figure supplement 1A, Supplementary File 4) are targets of Xbp1 in S. cerevisiae including a significant number of TF genes (n = 14; Figure 2-figure supplement 1B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the early response is likely to have influential effects on infection outcome, we focused on the four candidate TFs in Group 1 (induction at 0.5 h); the genes CAGL0F00561g, CAGL0G02739g , CAGL0L03157g and CAGL0J04400g are uncharacterized and annotated as the Saccharomyces cerevisiae orthologue of RPA12 , XBP1 , DAL80 , and HAP3 , respectively. Interestingly, three of the yeast orthologues ( RPA12 , XBP1 , DAL80 ) have negative roles in transcription (Mai & Breeden, 1997; Marzluf, 1997; Yadav et al , 2016). Transcription regulatory network analysis by PathoYeastract (Monteiro et al ., 2020) further showed that the orthologues of ∼35% macrophage infection-induced genes (n = 375 out of 1,078, respectively; Figure 2-figure supplement 1A, Supplementary File 4) are targets of Xbp1 in S. cerevisiae including a significant number of TF genes (n = 14; Figure 2-figure supplement 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, several uncharacterized TFs (CgXbp1, CgDal80 and CgRpa12) were strongly activated at the earliest infection stage. In S. cerevisiae , the orthologues of these TFs play negative regulatory roles (i.e., transcriptional repressors (Mai and Breeden, 1997; Marzluf, 1997; Yadav et al ., 2016)), suggesting the importance of transcriptional repression in shaping the overall transcriptional response to macrophages (Figure 7). This was confirmed by the precocious transcriptional activation of a large number of genes in the Cgxbp1 Δ mutant during macrophage infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Escherichia coli DH5␣ was used for cloning and plasmid propagation, and E. coli BL21-AI TM strains were used for heterologous protein expression. The msn2⌬ msn4⌬ strain used in this study was described previously (43). DH5␣ and BL21-AI TM cells were grown in LB broth medium containing 1% tryptone, 1% NaCl, and 0.5% yeast extract and incubated at 37°C.…”
Section: Role Of Msn2/msn4 In Yeast Fatty Acid Metabolism Yeast Straimentioning
confidence: 99%
“…; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0; Euroscarf msn2⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YMR037C::kanMX4 Euroscarf msn4⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YKL062W::kanMX4 Euroscarf dci1⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YOR180C::kanMX4 Euroscarf eci1⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YLR284C::kanMX4 Euroscarf fox2⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YKR009C::kanMX4 Euroscarf pot1⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YIL160C::kanMX4 Euroscarf pox1⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YGL205W::kanMX4 Euroscarf sps19⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YNL202W::kanMX4 Euroscarf pxa1⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YPL147W::kanMX4 Euroscarf pxa2⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YKL188C::kanMX4 Euroscarf cta1⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YDR256C::kanMX4 Euroscarf ctt1⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YGR088W::kanMX4 Euroscarf pex1⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YKL197C::kanMX4 Euroscarf pex3⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YDR329C::kanMX4 Euroscarf pex4⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YGR133W::kanMX4 Euroscarf pex5⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YDR244W::kanMX4 Euroscarf pex6⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YNL329C::kanMX4 Euroscarf pex7⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YDR142C::kanMX4 Euroscarf pex8⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YGR077C::kanMX4 Euroscarf pex10⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YDR265W::kanMX4 Euroscarf pex11⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YOL147C::kanMX4 Euroscarf pex13⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YLR191W::kanMX4 Euroscarf pex14⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YGL153W::kanMX4 Euroscarf pex15⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YOL044W::kanMX4 Euroscarf pex17⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YNL214W::kanMX4 Euroscarf pex18⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YHR160C::kanMX4 Euroscarf pex19⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YDL065C::kanMX4 Euroscarf pex21⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YGR239C::kanMX4 Euroscarf pex22⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YAL055W::kanMX4 Euroscarf pex25⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YPL112C::kanMX4 Euroscarf pex27⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YOR193W::kanMX4 Euroscarf pex29⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YDR479C::kanMX4 Euroscarf pex31⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YGR004W::kanMX4 Euroscarf oaf1⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YAL051W::kanMX4 Euroscarf adr1⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YDR216W::kanMX4 Euroscarf pip2⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YOR363C::kanMX4 Euroscarf snf1⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YDR477W::kanMX4 Euroscarf msn2msn4⌬ BY4741; Mat a; his3⌬ 1; leu2⌬ 0; met15⌬ 0; ura3⌬ 0;YMR037C::kanMX4;YKL062W::LEU2 Ref. 43…”
Section: Lipid Droplet Staining and Confocal Microscopyunclassified